Modernizing the Legal Framework for Surveillance : An Integrated Surveillance Decision. (Policy Papers; Policy Paper ;, 2012)
This paper proposes a draft Integrated Surveillance Decision (ISD) for adoption. As part of broader efforts to strengthen Fund surveillance, the Fund is modernizing its legal framework to better support operations. In April 2012, the Fund's Executive Board discussed Modernizing the Legal Framework for Surveillance-Building Blocks Toward an Integrated Surveillance Decision. That paper highlighted key weaknesses in the current legal framework for surveillance and provided proposals for addressing them. Most Directors agreed that introducing a new surveillance decision covering both bilateral and multilateral surveillance would help address these weaknesses. In particular, they agreed with the general proposed approach to fill the gaps in bilateral surveillance through multilateral surveillance.